Komunikasi Kepemimpinan Untuk Meningkatkan Kinerja Dalam Perspektif Ekonomi Islam (Study Kasus Pada UD Kaos Hasby) - Diah Ayu Rosanti; Amin Wahyudi (Niqosiya: Journal of Economics and Business Research, 2023)
Communication is an important element in a company. The source of information or communication sources mostly comes from leaders. A person's leadership has a great influence on the company. The aim of this research is to analyze the leadership practices carried out at UD Kaos Hasby from an Islamic economic perspective. This research uses a qualitative approach, namely research that is descriptive in nature and tends to use analysis. This research resulted in: 1) leadership communication practices carried out at UD Kaos Hasby. By focusing on the elements of communication, namely the message conveyed, the communicator, the communicant, the media used, and the consequences of the communication. 2) inhibiting factors and supporting factors for communication at UD Koas Hasby. The inhibiting factors are the lack of intensity of meetings between leaders and employees, as well as the lack of language skills possessed by some employees. Meanwhile, the supporting factors are leaders motivating employees and adequate facilities. 3) The impact of communication at UD Kaos Hasby is that it makes employee performance easier and problems can be resolved. From these several statements, the author concludes that the leadership communication that occurs at UD Kaos Hasby Mlarak is quite good and uses Islamic communication principles with Al-Qur'an themes, although there are several things that are obstacles and need to be improved.